11. QUALITY OF LIFE IN PATIENTS AFTER UNDERGOING TOTAL KNEE ARTHROPLASTY AT VIET DUC HOSPITAL 2025 (Vietnam Journal of Community Medicine, 2025)
Objective: This study aimed to describe and analyze the factors associated with health-related quality of life among patients six months after undergoing total knee arthroplasty at Viet Duc University Hospital in 2025.Subject and methods: A descriptive cross-sectional study was conducted on a sample of 108 patients who had undergone total knee arthroplasty. The WHOQOL-BREF instrument was utilized to assess. Relevant sociodemographic and clinical factors were also collected to examine their association with health-related quality of life.Results: The mean health-related quality of life score of patients after total knee arthroplasty was 60.62 ± 4.25. Among the domains, the highest health-related quality of life score was observed in the social relationships domain (65.97 ± 2.31), followed by the environment domain (63.19 ± 6.06), the physical health domain (57.97 ± 8.38), and the lowest was the psychological domain (55.36 ± 5.35). Factors including age, education level, comorbidities, anxiety, depression, pain, joint stiffness, and difficulty in performing daily activities were found to be significantly associated with the health-related quality of life of patients six months after total knee arthroplasty.Conclusion: Total knee arthroplasty can improve the health-related quality of life of patients with osteoarthritis. Information on factors-especially those that are significantly associated with health-related quality of life after surgery-can be considered to guide treatment based on individual patient characteristics. A better understanding of health-related quality of life and its associated factors can provide valuable insights into the effectiveness of interventions and lead to improved patient care.
Keywords: Quality of life; related factors; total knee arthroplasty.